2019
DOI: 10.24938/kutfd.429395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Systemic Inflammatory Parameters in Carbon Monoxide Poisoning

Abstract: Objective: The objective of this study is to examine systemic inflammatory blood parameters measured in complete blood count of patients with carbon monoxide (CO) poisoning and to evaluate the relation between the parameters and the severity of poisoning. Material and Methods: Our study is a retrospective case control study. Data was obtained through hospital automation system. Patients who were detected to have 10% and above carboxyhemoglobin levels were included in the study. Patients' complete blood count p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Leukocytes have been shown in previous adult studies to cause tissue injury connected with CO intoxication. 36 White blood cell, LYM, NEU, and NLR levels of COP cases were significantly higher compared with the control group, according to Tursun et al, Ertekin et al, and Emektar et al, [37][38][39] but no statistically significant correlation was found between the severity of COP and these parameters. Coşkun et al 18 discovered that circulating leukocyte, NEU, and LYM levels were significantly greater in adults with severe CO intoxication than in those with mild to moderate CO intoxication, implying that these elevated concentrations in the acute period were positively associated with high mortality in the short and long term.…”
Section: Discussionmentioning
confidence: 98%
“…Leukocytes have been shown in previous adult studies to cause tissue injury connected with CO intoxication. 36 White blood cell, LYM, NEU, and NLR levels of COP cases were significantly higher compared with the control group, according to Tursun et al, Ertekin et al, and Emektar et al, [37][38][39] but no statistically significant correlation was found between the severity of COP and these parameters. Coşkun et al 18 discovered that circulating leukocyte, NEU, and LYM levels were significantly greater in adults with severe CO intoxication than in those with mild to moderate CO intoxication, implying that these elevated concentrations in the acute period were positively associated with high mortality in the short and long term.…”
Section: Discussionmentioning
confidence: 98%